A Summary of Coronavirus Disease 2019: What We Should Know? - Ysrafil Ysrafil; Indwiani Astuti; Rosdiana Mus; Noviyanty Indjar Gama; Dwi Rahmaisyah; Riskah Nur'amalia (Tabriz University of Medical Sciences, 2020)
The emergence of Coronavirus Disease 2019 (COVID-19) has shifted the concerns of public health officials worldwide. Several previous studies have reported clinical features, methods of diagnosis and therapy approaches to combat the disease. Unfortunately, another problem arose in recognizing and distinguishing asymptomatic and presymptomatic patients who have a high risk of spreading the virus, which led health authorities to develop innovative strategies in mitigating the transmission of COVID-19. Known fever, cough, and myalgia with fatigue headache, hemoptysis, diarrhea and sometimes vomiting are the clinical features for patients confirmed with COVID-19. To confirm suspected patients, computerized tomography scan is the recommended modality since it has higher sensitivity. Several traditional approaches including antiviral, convalescent plasma therapy and monoclonal antibodies have been applied to combat the virus. Additionally, the application of several policies such as social distancing, recommendations for wearing masks and telemedicine were adopted to break the chain of the pandemic. There is much to learn from the many rapid advances in knowledge about this disease and we encourage everyone to always abide by health protocols recommended by healthcare providers so that this pandemic can end soon.